2014
DOI: 10.1145/2518175
|View full text |Cite
|
Sign up to set email alerts
|

Suffix Array Construction in External Memory Using D-Critical Substrings

Abstract: We present a new suffix array construction algorithm that aims to build, in external memory, the suffix array for an input string of length n measured in the magnitude of tens of Giga characters over a constant or integer alphabet. The core of this algorithm is adapted from the framework of the original internal memory SA-DS algorithm that samples fixed-size d-critical substrings. This new external-memory algorithm, called EM-SA-DS, uses novel cache data structures to construct a suffix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…dsa[ j] may be currently on disk and will be accessed slowly. To overcome this difficulty, the blockwise-induced sorting method reported in Beller et al [2013] and Nong et al [2014] can be applied to avoid random access of dsa [ j]. Blockwise-induced sorting evenly splits dsa into a number of blocks (the last block may be smaller).…”
Section: Inducing Solutionmentioning
confidence: 99%
See 4 more Smart Citations
“…dsa[ j] may be currently on disk and will be accessed slowly. To overcome this difficulty, the blockwise-induced sorting method reported in Beller et al [2013] and Nong et al [2014] can be applied to avoid random access of dsa [ j]. Blockwise-induced sorting evenly splits dsa into a number of blocks (the last block may be smaller).…”
Section: Inducing Solutionmentioning
confidence: 99%
“…Recently, work has been done on external memory SACAs. Recent experimental results have shown that algorithms based on the induced sorting principle, that is, eSAIS [Bingmann et al 2013] and EM-SA-DS [Nong et al 2014], are competitive against the previously best techniques such as DC3 [Dementiev et al 2008] and bwtdisk [Ferragina et al 2012]. 1 Let SA(x) denote the suffix array of x.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations